Culvert outlet Problems, Access Road, Erosion – Protection, Oudomxay Province - Chansavang, Vixay (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
One of the main purposes of the LRSP2 is to reduce poverty in Lao PDR through a sustainable improvement of local road net work with district and village participation. Road sections with unprotected embankment or filling slope have more or less problem with erosion. New materials have to be added every year to compensate the eroded part. Erosion on the slopes decreases the road stability which can lead to big damage and accidents. Problems occur at high filling slopes. Water from the culvert washes away filling material under the culvert which can lead to collapse of the culvert pipes and part of the road. This study analyses the erosion problems for slopes along the roads and try to find different methods for a good and cheap protection. Inventory of methods used in Laos and foreign countries. Site visits at roads with the case in question. Come up with different solutions and follow up the result. The result of this research was to write manual/ handbook with samples of different methods for slope protection and how /when they can be used. And Find cheap methods to prevent local erosion under culverts and write instructions that can be guidelines for future construction.